The Spine Surgical Care and Outcomes Assessment Program (Spine SCOAP): A Surgeon-Led Approach to Quality and Safety. Issue 5 (1st March 2015) - Lee, Michael J.; Shonnard, Neal; Farrokhi, Farrokh; Martz, Dean; Chapman, Jens; Baker, Ray; Hsiang, John; Lee, Chong; Gholish, Ray; Flum, David
Abstract : Study Design: Prospective registry of spine surgery. Objective: To identify variation in utilization, processes of care, and outcomes in spine surgery to improve statewide quality and safety. Summary of Background Data: Variability in the utilization and outcomes of elective spine surgery across different regions in the United States and internationally has become a growing focus of critical evaluation. In 2011, surgeons in Washington State created the Spine Surgical Care and Outcomes Assessment Program to address variability in use, process, and outcome of spine surgery. Methods: Prospective cohort study from consecutive spine fusion cases and 30% sampling of other spine procedures from up to 20 hospitals (2011–2013). Logistic regression models were developed using data from 10 quarters to determine factors associated with combined adverse events inclusive of index hospital death, reintervention, and adverse events not requiring intervention, and then applied to patients in the last 2 quarters. Results: A total of 10, 166 (58.9 ± 13.4 yr, 52.2% females) underwent surgery including 3767 (37%) lumbar and 6399 (63%) cervical procedures. Of the total, 75.3% of the cohort had a spine fusion and among those, neurological symptoms were described in 92.5% of patients, with baseline limb pain numeric rating scale (NRS) scores of 5.9 among those classified as having neurological symptoms. The NRS mean score for back pain was 5.9 with a mean Oswestry Disability Index/Neck Disability Index of 44. There was significant intersite variation in rates of cigarette smoking among patients undergoing fusion surgery (range, 0%–40%) and rates of combined adverse events with 10 hospitals having a significantly lower observed/expected ratio and 3 having a significantly greater observed to expected ratio. Conclusion: Spine Surgical Care and Outcomes Assessment Program identified significant variability in the indications, process of care, and outcomes related to spine surgery. This variability indicates the need for continued surveillance initiatives and point to opportunities for quality improvement and research. Level of Evidence: 2 Abstract : The Washington Spine Surgical Care and Outcomes Assessment Program is a statewide, surgeon-led, prospective spine registry created with the mission to identify variability in practice and to improve outcomes and quality of care rendered. As this registry continues to grow, this can serve as mechanism for initiating safety and quality improvement measures.